Esamojo laiko formantas -st- išvestiniuose latvių kalbos veiksmažodžiuose - Pakerys, Jurgis (Baltistica, 2009)
Latvian secondary verbs based on sta-presentsIn an earlier paper (Pakerys 2007), I presented a number of Lithuanian secondary verbal formations which are based on sta-presents, cf.: vargst‑áuti ‘to live in trouble, to have difficulties’, rūkst‑ė́ti ‘to emit smoke’, linkst‑úoti ‘to bend (intr.)’ beside var̃g‑st‑a ‘lives in poverty, takes trouble’, rū̃k‑st‑a ‘emits smoke’, liñk‑st‑a ‘bends (intr.)’, etc. I suggested that these formations could support the hypothesis which claims that the Lithuanian and Latvian iterative suffix -stī- arose due to the reanalysis of formations in -ī‑t(i) originally based on present stems in -sta (cf. competing denominative hypothesis which similarly proposes the reanalysis of formations in -ī‑t(i) which were originally based on nominal stems in -st-).In this paper, I tried to answer the question if secondary verbs based on sta‑presents are an exclusively Lithuanian phenomenon, or if they can be also found in Latvian. The data presented here were excerpted from the electronic edition of “Latviešu valodas vārdnīca” by Mülenbachs and Endzelīns (http://www.ailab.lv/MEV, accessed on 2007—2009) by searching for the verbs ending in ‑stāt(ies), -stēt(ies), -stīt(ies), ‑stināt(ies), and ‑stuot(ies). The main findings can be summarized as follows.The secondary verbal formations based on sta‑presents are also possible in Latvian, but they are very rare and non-regular, just as the Lithuanian ones. These formations belong to a broader group of (non-regular) nominal and verbal derivatives based on the present stems characterized by certain formatives or root vocalism. The closest parallel for the verbal formations which include the present formative -st- can be found in some adjectives in -īgs, cf.: birst‑īgs ‘friable’, (ne)mir̃st‑îgs ‘(im)mortal’ beside bir̃‑st‑u ‘I fall (of small objects)’, (ne)mir̃‑st‑u ‘I (do not) die’, etc. (Blinkena 1984).As far as specific verbal suffixes are concerned, the number of examples and their interpretation varies. To start with, I was unable to find any formations ending in ‑stāt or ‑stuot which would be based on sta‑presents. On the other hand, it is worth noting that an independent suffix -stāt is possible in two formations, cf. je̦m̃‑stâ‑t ‘wiederholt nehmen; to take repeatedly’ beside je̦mu, jẽmu, jem̃t ‘nehmen; to take’ and žã‑stâ‑tiês ‘gähnen; to yawn’ beside Lith. žióti(s) (-ja(si)) ‘to open (one’s mouth)’. These examples possibly reflect a well-known variation of present stems in *‑ā and *‑āja, cf. Lith. mė́tyti, mė́to beside (rare) mė́toti, mė́toja, Latv. mę̃tât, mę̃tãju, OCS mětati, mětajǫ, etc. Some verbs ending in -stuot have primary counterparts with present sta-stems, but these formations are most probably just some variants alongside verbs in -stīt. So just as there is lakstuôt ‘springen; to jump’ beside lakstît ‘idem’, one finds cīkstuôtiês ‘kämpfen, ringen; to fight’ beside cīkstîtiês ‘idem’ and the primary verb cīk‑st‑uôs, cijuos, cīties ‘idem’.The development of some verbs ending in -stēt was already described by Endzelīns (1951, 761). He suggested that in a number of cases, the present stem formative -st- was reanalyzed as a part of the lexical stem and the suffix -ē‑ was introduced in the infinitive and the preterit stems, cf. drì(k)st‑êt, drì(k)st‑u, drì(k)st‑ẽju ‘dürfen, wagen, sich unterstehen; to be allowed, to dare’ alongside Lithuanian drį̃s‑ti, drį̃{s}‑sta, drį̃s‑o ‘to dare’. Therefore, these cases also illustrate the possibility to create verbs on the basis of present stems in -sta, but they have to be regarded as a certain reshaping of the same words rather than a derivation (i.e. the formation of new lexical items with certain derivational meaning beside their base words). The only possible iterative formations (not mentioned in Endzelīn’s list) are tupst‑êtiês ‘sich wiederholt hinhokken; to squat down (intr.) repeatedly’ beside tup‑st‑u(ôs) (tupju(ôs), tūpu(ôs) are also attested), tupu(ôs), tupt(iês) ‘(sich nieder)hocken; to squat down (intr.)’ and sprãkst‑êt (spārgst‑êt) ‘mit Knall bersten; to crackle, to sputter’ alongside sprâg‑st‑u, sprâgu, sprâgt ‘bersten, platzen; to burst’ (already mentioned by Leskien 1902/1903, 172).There are 5 verbs ending in -stināt which are based on sta‑presents. All of them have causative meaning, cf.: ir̃st‑inât ‘auftrennen (eine Naht); to undo (a seam) : ir̃‑st‑u, iru, ir̃t ‘sich auf‑, lostrennen, sich bröckeln; to disintegrate’; kalst‑inât ‘hungern lassen; to make starve’ : kàlt‑st‑u, kàltu, kàlst ‘mager werden, verkommen; to grow weaker, thinner’; pĩkst‑inât ‘zörgen, zum Zorne reisen; to make anger’ : pîk‑st‑u, pîku, pîkt ‘zornig, böse werden; to become angry’; sprāgst‑inât ‘aufplatzen machen; to make burst’ : sprâg‑st‑u, sprâgu, sprâgt ‘bersten, platzen; to burst’; pazīst‑inât ‘bekannt machen; to acquaint’ : pazĩ‑st‑u, pazinu, pazĩt ‘erkennen; to know, to be acquainted’. In all cases the present stems of the base verbs have no variants, so these examples have to be regarded as quite reliable.The interpretation of verbs ending in -stīt is rather complicated. The iterative suffix -stīt is itself quite productive, and the fact that some base verbs have present sta‑stems could be just a coincidence. However some formations have causative meaning which is not typical for the suffix -stīt. Therefore, these verbs have to be derivations in -īt based on the present stems in -sta, cf. gul̃st‑ît ‘niederlegen; to lay, to put down’ : gul‑st‑u (also guļu), gulu (also gūlu), gul̃t ‘sich lagern; lie down’; līkst‑ît ‘to sway, to rock’ : lìk‑st‑u, lìku, lìkt ‘sich biegen, krumm werden; to bend’; ìetupst‑ît ‘nachlässig hineinsetzen; to put in carelessly’ : *ìetup‑st‑u (the prefixed stem in -sta is not attested in the dictionary, but cf. tup‑st‑u beside tupju, tūpu), ìetupu, ìetupt ‘sich hineinhocken, sich herein‑, hineinsetzen; to squat into’.In conclusion, the data presented here and in Pakerys 2007 show that both Latvian and Lithuanian have some deverbative formations based on the present stems in -sta. There seem to be no reliable examples of common East Baltic formations of this type (cf. only Latvian rim̂stît‑iês2 ‘wiederholt still od. ruhig werden; to calm down (intr.)’ beside Lithuanian nu‑rìmstyti ‘to calm down (trans.)’), but the possibility to use the present stems with certain formatives as the base of derivation is clearly shared by both languages. These formations support the deverbative hypothesis of the origin of the Lithuanian and Latvian iterative suffix -stī-, but it also does not imply that the denominative hypothesis has to be rejected.
Keywords: latvių kalba; veiksmažodis; išvestinis; -st-; esamasis laikas